Bacterial degradation of monocyclic aromatic amines - Arora, Pankaj K. (Frontiers in Microbiology, 2015)
Aromatic amines are an important group of industrial chemicals, which are widely used for manufacturing of dyes, pesticides, drugs, pigments, and other industrial products. These compounds have been considered highly toxic to human beings due to their carcinogenic nature. Three groups of aromatic amines have been recognized: monocyclic, polycyclic and heterocyclic aromatic amines. Bacterial degradation of several monocyclic aromatic compounds has been studied in a variety of bacteria, which utilizes monocyclic aromatic amines as their sole source of carbon and energy. Several degradation pathways have been proposed and the related enzymes and genes have also been characterized. Many reviews have been reviewed toxicity of monocyclic aromatic amines; however, there is lack of review on biodegradation of monocyclic aromatic amines. The aim of this review is to summarize bacterial degradation of monocyclic aromatic amines. This review will increase our current understanding of biochemical and molecular basis of bacterial degradation of monocyclic aromatic amines.